INTEGRATED COMMUNICATION IN THE DIGITAL ERA AFFECTING PUBLIC PERCEPTION OF GOVERNMENT INFORMATION: A CASE STUDY OF THE LOCAL GOVERNMENT ORGANIZATION IN LAN SAKA DISTRICT, NAKHON SI THAMMARAT PROVINCE - Nakornpat, Wissanupong; Srinounpan, Chawanrat; Srinounpan, Bamrung; Jumnian , Korrakot (Journal of Graduate School Sakon Nakhon Rajabhat University, 2025)
The objectives of this research were to: 1) examine the communication patterns of Local Government Organizations (LGOs) in Lan Saka District, Nakhon Si Thammarat Province; 2) analyze the communication patterns perceived as effective by service users of these LGOs; and 3) develop the communication patterns for these LGOs. This research employed a mixed–methods approach, combining qualitative research through in–depth interviews with six individuals responsible for organizational communication and public relations, which identified 13 communication patterns currently in use. For the quantitative component, the 13 communication patterns were used to design a survey and to determine the most suitable patterns from a sample of 402 service users. Data analysis employed descriptive statistics: percentage, mean, and standard deviation. Results indicated that the top six communication patterns preferred by service users were through Facebook ( = 4.43), LINE ( = 4.32), websites ( = 4.14), wired loudspeaker systems/community radio /community audio towers ( = 4.13), personal contact ( = 4.08), and projects/activities ( = 4.01). The findings also highlighted a preference for an integrated communication approach that combined both traditional and digital methods.